1992
DOI: 10.1002/art.1780350113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Analysis of HLA—DR and HLA—DQ Genes Among Anti—U1‐70‐kd Autoantibody Positive Connective Tissue Disease Patients

Abstract: Objective. We have recently found that the presence of autoantibodies against the 70-kd polypeptide of U1 RNP (Ul-70-kd) is associated with HLA-DR4 and DR2. To further characterize this association, we performed a molecular genetic analysis of HLA-DR and DQ genes among patients with autoantibodies against Methods. The polymerase chain reaction (PCR), sequence-specific oligonucleotide hybridization, and U1-70-kd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 53 publications
2
37
2
1
Order By: Relevance
“…In contrast, evidence of a primary association with the HLA-DR locus is provided by our study and that by Kaneoka et a1 (40). Among our patients, all but 1 of those whose disease remained undifferentiated had either HLA-DR2 or DR4.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In contrast, evidence of a primary association with the HLA-DR locus is provided by our study and that by Kaneoka et a1 (40). Among our patients, all but 1 of those whose disease remained undifferentiated had either HLA-DR2 or DR4.…”
Section: Discussioncontrasting
confidence: 48%
“…The association with more than one HLA allele may be explained by the shared epitope hypothesis as in RA (33). In the molecular genetic analysis study by Kaneoka et al, an association was found between the presence of autoantibodies to the 70-kd polypeptide and a shared epitope that was present exclusively on most HLA-DR2 and DR4 subtypes (excluding DRB1*1601 and *1602 subtypes of DR2 and *0402 subtype of DR4) (40). The epitope consists of 7 amino acids at the HLA-DRB 1 region.…”
Section: Discussionmentioning
confidence: 99%
“…Subfamilyspecific PCR was performed as described above and the products were subjected to gel isolation and direct DNA sequencing as described previously [14,22]. In brief, the amplified DNA was isolated from a 5% polyacrylamide gel using ammonium acetate and EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies assessing potential HLA phenotypic associations with the anti-Sm and anti-RNP responses have been few in number, of limited sample size, and often did not distinguish between patients with anti-Sm and/or anti-RNP (6,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Moreover, the serologic HLA typing employed in these studies is unable to detect the more extensive polymorphisms of HLA class I1 alleles, which is now possible with molecular methods.…”
mentioning
confidence: 99%